Mucin Reactivity after Acute Exposure to Mercury and Zinc Chloride in Neurocytes of Freshwater Snail Bellamya bengalensis: A Histochemical Study. (2nd October 2014) - Londhe, Sunil; Kamble, Nitin
Abstract : Central nervous system (CNS) of gastropods is extensively studied for its pathology and immunocytology; there is scanty information on histochemical alterations in neuronal cells due to heavy metal. This study was designed to investigate histochemical alterations in cerebral neurons of freshwater snail Bellamya bengalensis after intoxication with mercuric chloride (HgCl2 ) and zinc chloride (ZnCl2 ). As per chemical components cerebral ganglia of Bellamya bengalensis showed three different zones, namely, periganglionic connective tissue sheath, interperikaryonal space, and neuropil. After intoxication, increased acidic content in extracellular matrix (ECM) of neuronal cells was found. These alterations were directly proportional to time of exposure period. From results, HgCl2 proved its highly toxic nature over chemical composition of cerebral neuronal cells of freshwater snail Bellamya bengalensis compared to ZnCl2 intoxication.